2012
DOI: 10.1590/s0103-84782012000900020
|View full text |Cite
|
Sign up to set email alerts
|

Modelos de regressão aleatória para avaliação da curva de crescimento em matrizes de codorna de corte

Abstract: 10, 70, 140, 210, 280, 350, 420, 770, 1120

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The polynomial regression model presented high explanatory power (R² = 99.99%), low AIC = -24.68 and SSR = 2.5 and greater Willmott index (d = 0.9999) than the other models evaluated (Table 3). Similar results were found by Bonafé et al (2011) and Teixeira et al (2012a) who studied mating of cut quails belonging to the genetic groups UFV1 and UFV2.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The polynomial regression model presented high explanatory power (R² = 99.99%), low AIC = -24.68 and SSR = 2.5 and greater Willmott index (d = 0.9999) than the other models evaluated (Table 3). Similar results were found by Bonafé et al (2011) and Teixeira et al (2012a) who studied mating of cut quails belonging to the genetic groups UFV1 and UFV2.…”
Section: Resultssupporting
confidence: 89%
“…Drumond et al (2013) verified that the logistic and Gompertz models presented the best results to explain the growth of male and female quails. Bonafé et al (2011) and Teixeira et al (2012a) verified that the weight growth of quails can be explained by Legendre polynomial models.…”
Section: Introductionmentioning
confidence: 98%
“…Accordingly, Teixeira et al . (), when evaluating the growing curve of meat‐type quails from two strains (UFV1 and UFV2), concluded that models with heterogeneous residual variance with three and five classes were the most adequate to the UFV1 and UFV2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Assis et al (2006) found a better adjustment when using models with four residual variances' classes as these models were less parameterized. Accordingly, Teixeira et al (2012), when evaluating the growing curve of meat-type quails from two strains (UFV1 and UFV2), concluded that models with heterogeneous residual variance with three and five classes were the most adequate to the UFV1 and UFV2, respectively. For most carcass traits, genetic correlations between predicted breeding values at different nutritional environments were positive and high in both strains, except for BW at slaughter and breast weight for the LF2 strain, which presented values below 0.80, thus indicating the presence of G 9 E interaction (Figure 1).…”
Section: Resultsmentioning
confidence: 99%